Tobacco Knowledge, Attitudes, and Services Among Latino/a Community Health Workers - Enrique Villacis Alvarez; Lian Nicholson; Dario Villamar; Clarissa Huard; Anna Veluz-Wilkins; Marcia Tan (SAGE Publishing, 2023)
Background: Tobacco-related illnesses are among the leading preventable causes of death for Latinos/as in the United States. Latino/a groups are less likely to receive advice to quit from health professionals or use tobacco cessation strategies. The position of community health workers (CHWs) warrants further attention to address tobacco-related disparities in Latino/a communities. The objective of this study was to describe CHWs' roles to inform future smoking cessation training to ensure relevance and accessibility. Methods: A needs assessment survey, including a 10-item tobacco knowledge questionnaire, was conducted with 29 Latino/a CHWs serving Latino/a communities in a metropolitan area to assess their roles, tobacco related services, attitudes, and knowledge. Results: All CHWs were Spanish-speaking and mainly employed part time (55%) in community organizations (67%). They offered various services, primarily health education. Most of the CHWs (58.6%) assessed and discussed tobacco use, yet half (51.7%) reported low confidence in this area. Some CHWs (41%) expressed that their clients/patients would use evidence-based nicotine replacement therapies as a smoking cessation treatment if offered and identified "Financial Cost" (31%) as a deterrent of use. CHWs' score on a tobacco knowledge questionnaire indicated low knowledge in areas related to tobacco (4.03 out of 10; SD = 1.92). Conclusions: CHWs reported low tobacco related knowledge and confidence, and would benefit from tailored tobacco cessation training to decrease tobacco cessation disparities.